Hazard Analysis Critical Control Points (HACCP) – Principle 1: Conduct a Hazard Analysis - Ronald H. Schmidt; Debby Newslow (EDIS, 2007)
FSHN07-03, a 10-page fact sheet by Ronald H. Schmidt and Debby Newslow, defines food hazards and explains the process of conducting a hazard analysis in order to fulfill HACCP Principle 1. Published by the UF Department of Food Science and Human Nutrition, July 2007.